2018
DOI: 10.1111/jocs.13968
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin therapy in cardiac surgery

Abstract: Background Arginine vasopressin (AVP) is a naturally occurring peptide with diverse effects mediated through selective V1 and V2 receptors. About 10% of patients undergoing cardiopulmonary bypass develop postoperative vasodilatory shock requiring high‐dose catecholamines. We sought to examine the role of AVP therapy in cardiac surgery. Methods A search of Medline was conducted through September 2018 using key words and medical subject headings (MeSH) relating to AVP, copeptin, and cardiac surgery. A systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
(119 reference statements)
0
3
0
3
Order By: Relevance
“…Reasons for avoiding enteral feeding may relate to the severity of the patient's baseline clinical condition rather than to the use of AVP, especially as most AVP users felt AVP was a second-line medication. Porcine models have shown a decrease in blood flow in the gastric mucosa after cardiopulmonary bypass, exacerbated by the use of AVP ( 9 , 22 ), which could pose a theoretical risk of necrotizing enterocolitis. However, Alten et al reported no cases of necrotizing enterocolitis and adequate tolerance of enteral feeds in all patients with early initiation of AVP after cardiovascular bypass surgery ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for avoiding enteral feeding may relate to the severity of the patient's baseline clinical condition rather than to the use of AVP, especially as most AVP users felt AVP was a second-line medication. Porcine models have shown a decrease in blood flow in the gastric mucosa after cardiopulmonary bypass, exacerbated by the use of AVP ( 9 , 22 ), which could pose a theoretical risk of necrotizing enterocolitis. However, Alten et al reported no cases of necrotizing enterocolitis and adequate tolerance of enteral feeds in all patients with early initiation of AVP after cardiovascular bypass surgery ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of all, the increase in copeptin levels at baseline could reveal an advanced stage in the V1R desensitization process as described in severe HF, thus predicting the enormous need for AVP during the PCVS to overcome a rapidly increasing peripheral insensitivity. Recently, several studies have suggested that the use of 1-desamino-8- d -arginine-vasopressin (dDAVP) in this setting would reduce the need for high doses of NE and related adverse effects [ 29 ]. A recent meta-analysis showed that the precocious administration of low dose of dDAVP would reduce the rate of perioperative complications in patients undergoing elective and emergency cardiac surgery (OR 0.33, 95% CI 0.20–0.54) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCVS represents a serious complication after CPB, requiring a large amount of vasoactive agents, often burden by relevant side effects. The presurgical identification of subjects at high risk of developing PCVS would be useful in order to select these patients to a precocious usage of 1-deamino, 8-D arginine-vasopressin (dDAVP) in case of hypotension induced by CPB [28]. A recent meta-analysis of 8 randomized controlled trials showed that a low dose of dDAVP would reduce the rate of perioperative complications in patients undergoing elective and emergency cardiac surgery (OR 0.33, 95% CI 0.20-0.54) [29].…”
Section: Discussionmentioning
confidence: 99%